Family Effort in Fulfilling Personal Hygiene for Mental Disorder People - Suprajitno Suprajitno; Khabibah Jannatul Firdaus; Imam Sunarno (STIKes Patria Husada Blitar, 2017)
Personal hygiene is a necessity of every person including people with mental disorder. People who are able to fulfill his needs during lives at home is family. The main personal hygiene that needs to be fulfilled is the hygiene of the body and the welfare of the physical and psychological. Research purposes was to know the family effort to fulfilling for personal hygiene of people with mental disorder. The research design used descriptive. The research population were families who have’s members with mental disorder who are registered at public health center of Kepanjen Kidul of Blitar City. Samples size were 30 families selected by purposive sampling. Time of data collected on the Mei 31st until July 30th, 2017. The result showed that the family effort was as good as 24 families (80.0%), enough as much as 5 families (16.7%), and less as much as 1 family (3.3%). Personal hygiene of person with mental disorder needs that are the needs of dress and toilet. Recommended to maintained of family efforts to fulfill of his personal hygiene need using health education by health provider.